1994
DOI: 10.1364/ao.33.007397
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of normal and carcinomatous bronchial tissue

Abstract: To understand better the optical characteristics and autofluorescence properties of normal and carcinomatous bronchial tissue, we measured the absorption coefficient, scattering coefficient, and anisotropy factor from 400 to 700 nm. We made the measurements by using an integrating sphere with a collimated white-light beam to measure total reflectance and transmittance of samples. The unscattered transmittance of the samples was measured through polarized on-axis light detection. The inverse adding-doubling sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 18 publications
5
79
0
Order By: Relevance
“…3(c)]. The calculated values for l s and F th compare favorably to Qu et al, 28 who found l s ≈ 50 μm for bronchial tissue epithelium at 700 nm, and our previous finding of F th ¼ 1.6 J∕cm 2 in porcine vocal folds after accounting for the difference in pulse width. 17,18 A high level of consistency in the measured values across the tissues examined, even with variations in the epithelial thickness, makes it possible to predict the E th;surf ðz ab Þ curve for new vocal fold tissues simply by measuring z ep .…”
supporting
confidence: 86%
“…3(c)]. The calculated values for l s and F th compare favorably to Qu et al, 28 who found l s ≈ 50 μm for bronchial tissue epithelium at 700 nm, and our previous finding of F th ¼ 1.6 J∕cm 2 in porcine vocal folds after accounting for the difference in pulse width. 17,18 A high level of consistency in the measured values across the tissues examined, even with variations in the epithelial thickness, makes it possible to predict the E th;surf ðz ab Þ curve for new vocal fold tissues simply by measuring z ep .…”
supporting
confidence: 86%
“…For near infrared light in tissue, scattering is the dominant attenuation mechanism [11], and the scattering coefficient µ s is typically a factor of 10-100 times larger than the attenuation coefficient µ a [12]. For the 1325 nm wavelength used in the experiments of this report, μ a for pure water is 0.149 mm -1 .…”
Section: Optical Properties Of Tissuementioning
confidence: 89%
“…One of the major causes for the loss of autofluorescence in areas of dysplasia or cancer is found to be a decrease in the extracellular matrix content. 35 A recent study showed that a proportion of the dysplasia or cancer lesions expressed matrix metalloproteinases that could degrade the extracellular matrix. 36 Fluorophores, such as porphyrin, flavins, and nicotinamide adenine dinucleotide (NADH), are involved in cellular metabolic processes.…”
Section: Mechanisms Of Different Autofluorescence Intensities In Normmentioning
confidence: 99%